COMPARISON OF EMERGENCY AND ELECTIVE INTERVENTION WITH SEMI-RIGID URETEROSCOPIC LITHOTRIPSY FOR PATIENTS WITH URETERAL CALCULI - Muhibullah Bangash; Nazim, Syed Muhammad; Nasir Khan; Muhammad Owais Abdul Ghani; Suniya Naeem (Journal of Ayub Medical College Abbottabad, 2022)
Background: Ureteroscopy (URS) is a safe and highly effective treatment option for treatment of ureteral calculi. With the advancement of technology, there is also expansion of its indications including use in early or emergency setting. This study aims to compare safety and efficacy of emergency ureteroscopy (EmURS) versus elective ureteroscopy (ElURS) for ureteral stones. Methods: Patients with unilateral single radio-opaque ureteral stone who underwent semi-rigid URS from January 2008 till December 2019 were included. Patients with solitary kidney, uro-sepsis, pregnancy or pre-operative drainage with nephrostomy or JJ stent were excluded. EmURS was defined as URS being performed within 48 hours of presentation, while ElURS was defined as URS performed after failed medical expulsive therapy. Patient, stone and outcome related variables were compared in both groups. Stone free rate was defined as no evidence of stone on plain x-ray KUB after 1 week. Results: We compared 132 patients in EmURS group against 264 in ElURS group. Age, gender, comorbidities, stone location, laterality and mean stone size were comparable in both groups. EmURS had a less median operative time (p=0.05). Stone free rate achieved was 90.2% in EmURS and 87.1% in ElURS, respectively (p=0.38). Double J stent was placed in 44.7% and 46.2% of EmURS and ElURS respectively (p=0.89). Ancillary procedures were performed in 9.8% of EmURS and 11.7% of ElURS (p=0.57). Overall complication rates were reported in 7.6% in EmURS and 11.7% in ElURS (p=0.22) and most were Clavien grade 1. Conclusion: Emergency URS for ureteral stones is a safe and effective one-stage definitive treatment option for patients with acute renal colic not responding to conservative management